Towards “Post-Digital”. A Media Theory to Re-Think the Digital Revolution - Striano, Francesco (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2019)
Can we say we live in a post-digital condition? It depends. This paper sets out to distinguish between the current mass digital culture and an authentic post-digital culture. If we mean “post-digital” as the full internalization and awareness of the result of the so-called digital revolution, then it is necessary a philosophical work to discuss related problems, identify the causes and propose solutions. An authentic philosophy of digital will, however, have to start from a clarification of the terms and basic objects of its investigation. Here media theory is inserted as an analytical tool: the purpose of this essay is to outline a road map for a good media theory that interfaces with questions of definition of digital, also in light of the notions of space, time, and matter. As will be seen, the description given here for a “good media theory” does, in fact, coincide with an already existing – and inserted in the contemporary debate – school. In conclusion we will try to delineate the field of philosophical inquiry opened by the clarification brought by the previous analysis, and to suggest a general framework within which philosophy will have to move in order to finally reach the authentic post-digital condition.
Keywords: CMC; digital; information; media; theory